VÀI NÉT VỀ ĐỊA CHẤT - ĐỊA MẠO BÁN ĐẢO BARTON VÀ WEIVER, ĐẢO KING GEORGE, NAM CỰC - Lâm, Doãn Đình (Vietnam Journal of Earth Sciences, 2011)
Some geological and geomorphological features of the Barton and Weiver peninsula, King George Island, Antarctica Barton and Weiver peninsula, King George Island situated at periphery of Antarctica, where many scientific research stations have been set up. Gently dipping to the south and southwest, Cretaceuos-Paleogene volcaniclastic of the Sejong Formation is well spread on this peninsula with thickness about 100m. The Formation composes of 5 facies: 1/ disorganised, matrix-supported conglomerate; 2/ disorganised, clast-supported conglomerate; 3/ stratified, clast supported conglomerate; 4/ thin-bedded sandstone and 5/ tuff lapili. Quaternary deposits are moraine, tills on low-lying hills and gravels, cobbles, on the recent marine terrace or beach. Intrusive rocks in this area are granodiorite, diorite, gabbro and quartz monzodiorite that intruded the Sejong Formation and basaltic andesite. Effusive rocks are most spread in Barton and Wiever peninsula; consist of basalts and basaltic andesite. In study area, glacial relief is very common, consists of low-lying hills (150-200m height) and cliffs. There are recent marine terraces (2-3m height) and beach situated around peninsula, covered by very course deposits.